Where You Live Matters to Have the American Dream: The Impact of Collective Social Capital on Perceived Economic Mobility and the Moderating Role of Income - Kim, Yanghee; Yi, Youjae; Bak, Hyuna (Asia Marketing Journal (Online), 2021)
The current research develops and tests the theory that beliefs in economic mobility are affected by social capital at the community level, especially for low-income individuals. Integrating concepts from social capital and perceived economic mobility (PEM), this research hypothesizes that members of disadvantaged groups (vs. members of advantaged groups) are more likely to adjust their PEM depending on the social capital at the community level. Using archival data, multilevel analysis is employed to examine whether individual- or community-level social capital increases PEM and the extent to which income moderates this relationship. Consistent with our hypotheses, social capital at the community level is significantly associated with PEM and this relationship is stronger for low-income (vs. high-income) earners. Study 1 shows that individuals in communities with high levels of social relations and participation are more likely to have higher PEM than those in communities with lower levels. Study 2 replicates this finding with a similar dependent variable: negative prospects. Further, the PEM-enhancing and negative prospects-decreasing effects of community-level social capital are consistently stronger for low-income (vs. high-income) earners. This study extends the investigation of PEM and social capital by suggesting social capital as a possible antecedent of PEM.